Proteomics Analysis of Cancer Exosomes Using a Novel Modified Aptamer-based Array (SOMAscan(TM)) Platform - Webber, Jason (The American Society for Biochemistry and Molecular Biology, 2014)
We have used a novel affinity-based proteomics technology to examine the protein signature of small secreted extracellular vesicles called exosomes. The technology uses a new class of protein binding reagents called SOMAmers® (slow off-rate modified aptamers) and allows the simultaneous precise measurement of over 1000 proteins. Exosomes were highly purified from the Du145 prostate cancer cell line, by pooling selected fractions from a continuous sucrose gradient (within the density range of 1.1 to 1.2 g/ml), and examined under standard conditions or with additional detergent treatment by the SOMAscan(TM) array (version 3.0). Lysates of Du145 cells were also prepared, and the profiles were compared. Housekeeping proteins such as cyclophilin-A, LDH, and Hsp70 were present in exosomes, and we identified almost 100 proteins that were enriched in exosomes relative to cells. These included proteins of known association with cancer exosomes such as MFG-E8, integrins, and MET, and also those less widely reported as exosomally associated, such as ROR1 and ITIH4. Several proteins with no previously known exosomal association were confirmed as exosomally expressed in experiments using individual SOMAmer® reagents or antibodies in micro-plate assays. Western blotting confirmed the SOMAscan(TM)-identified enrichment of exosomal NOTCH-3, L1CAM, RAC1, and ADAM9. In conclusion, we describe here over 300 proteins of hitherto unknown association with prostate cancer exosomes and suggest that the SOMAmer®-based assay technology is an effective proteomics platform for exosome-associated biomarker discovery in diverse clinical settings.